A parametric analysis of future climate change effects on the energy performance and carbon emissions of a Chinese prefabricated timber house. (March 2023) - Zhang, Xi; Du, Jiangtao; Sharples, Steve
Prefabricated timber houses have received growing attention in China recently as being one possible approach to mitigating climate change impacts. This article presents the results from a dynamic thermal simulation parametric analysis of building characteristics and primary energy consumption, embodied and operational carbon of newly built prefabricated timber house types in northern China for current and future climates (2050 and 2080). The dynamic thermal modelling software DesignBuilder (+EnergyPlus) was adopted as the simulation package. The main findings from the study were: (i) by 2080 climate change could increase energy demand by 13% for a terraced house, by 10% for a semi-detached house, and by 6% for a detached house, with corresponding increased carbon emissions of 27%, 26% and 23% respectively; (ii) in 2080, a terraced house would achieve 74% energy demand and 90% carbon emissions of a detached house; (iii) increasing the window-to-wall ratio from 0.25 to 0.45 would lead to 31% increase in energy demand, and 42% increase in carbon emissions in 2080; (iv) adjusting the configuration of key timber structural components (walls and floors) could lead to reductions of 19% in primary energy demand, 23% in operational carbon, and 6% in embodied carbon. Practical applications : A terraced timber house with south-facing and a window-to-wall ratio of 0.25 would be an optimal configuration to mitigate climate change impacts in northern China. The adjustment of prefabricated timber wall structure could give rise to significant reductions in primary energy consumption, operational carbon emissions, and embodied carbon.